A modified TPU nanofiber membrane and preparation method thereof

By adding a modifier with a fluorine-containing hydrophobic structure to the TPU resin and adjusting the humidity during the spinning stage, the problem of difficult coordination between high permeability and high selectivity of the existing full heat exchange membrane is solved, and the hydrophobicity, mechanical properties and moisture permeability of the modified TPU nanofiber membrane is improved, meeting the efficient operation needs of the full heat exchanger.

CN117364344BActive Publication Date: 2025-04-01ZHEJIANG DONGHUA NANOTECHNOLOGY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311285430.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-01
Estimated Expiration
2043-10-07

AI Technical Summary

Technical Problem

The existing full heat exchange membranes are difficult to coordinate between high permeability and high selectivity, and have low mechanical strength, which makes them prone to powder or slag drops, which cannot meet the latest requirements of full heat exchangers.

Method used

By adding a modifier with a fluorine-containing hydrophobic structure to the TPU resin and adjusting the humidity during the spinning stage, the enrichment of the modifier and the pore structure of the film are controlled, thereby regulating the densified pore structure of the membrane and improving mechanical properties, moisture permeability and hydrolysis resistance.

Benefits of technology

The hydrophobicity, mechanical properties and moisture permeability of the modified TPU nanofiber membrane are improved, which avoids the hydrolysis of TPU molecules, reduces deformation, and meets the efficient operation needs of the full heat exchanger.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a modified TPU nanofiber membrane and a preparation method thereof, wherein a large number of fluorinated biphenyl structures exist on the surface of the modified TPU nanofiber membrane, and the fluorinated biphenyl structures are enriched on the surface of the modified TPU nanofiber membrane by controlling the humidity conditions. By regulating the content of the fluorinated biphenyl compound and the spinning humidity, the formation of a densified pore structure inside the modified TPU nanofiber membrane is achieved, and finally the hydrophobicity of the modified TPU nanofiber membrane is improved, while the mechanical properties of the fiber are not weakened, so that the modified TPU nanofiber membrane has excellent tensile stress and reduced deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermoplastic polyurethane fiber membranes, and in particular to a modified TPU nanofiber membrane with a pore structure regulated by humidity and a preparation method thereof. Background Art

[0002] As epidemic diseases such as SARS and H1N1 threaten people's lives, improving indoor air quality has received great attention. Fresh air circulation is still an effective and economical way to improve indoor air quality. However, the energy consumption of processing fresh air accounts for 20-40% of the total energy consumption of air conditioning. In the hot and humid summer in southern my country, this energy consumption is even much higher. In order to effectively save energy, HVAC researchers have been constantly seeking a low-energy fresh air heat and moisture recovery process for decades. Membrane dehumidification and membrane heat and moisture recovery have aroused great interest among researchers due to their advantages such as no corrosion problems, no valve switching, no moving parts, high system reliability, easy maintenance, and low energy consumption.

[0003] The total heat exchanger is a key technology for fresh air full heat recovery. This device is like installing a flat plate heat exchanger between the fresh air channel and the indoor exhaust channel. In summer, the outdoor fresh air is often wet and hot, while the indoor exhaust air is dry and cool. After the fresh air and exhaust air exchange heat and moisture in the total heat exchanger, the fresh air can reach a state close to the indoor air, saving the load required for fresh air dehumidification and refrigeration; in winter, the fresh air is dry and cold, while the indoor exhaust air is warm and moist. After passing through the total heat exchanger, the fresh air becomes warmer and moister, and also reaches a state close to the indoor air, saving heating and humidification energy consumption, and also saving fresh air load, so that the energy consumption of air conditioning processing fresh air is saved by 70% to 80%. The biggest advantage over traditional metal heat exchangers is that this membrane can not only recover sensible heat, but also effectively recover latent heat while ensuring that the dirty gas in the indoor exhaust air does not penetrate.

[0004] The US patent No. WO03041844 proposes to use a steam membrane to dehumidify the air. The steam membrane has a high selective permeability. When the air flow containing water vapor passes through the steam membrane in a convection or countercurrent manner, the water vapor will pass through the membrane. Due to the partial pressure difference of the water vapor, the water vapor will be discharged with a purge airflow. The purge airflow has a lower water vapor partial pressure difference than the inlet air flow. The Japanese patent No. JP11090194 proposes to use a polyetherimide membrane to dehumidify the air. The polyetherimide dehumidification membrane is a hollow fiber membrane. The hollow fiber membrane is a mixture of polyether, imide-polyetherimide, and imide. The inner surface of the membrane is preferably coated with a layer of polyvinyl pyrrolidone or a layer of moisturizer. The membrane can effectively inhibit the formation of cavitation and improve durability.

[0005] Since the diffusion coefficient of solute in solid (<10-8 cm 2 / s) is very small. The biggest disadvantage of existing membranes is that it is difficult to coordinate the contradiction between high permeability and high selectivity, and the preparation cost is too high. In addition, the mechanical strength of existing membranes is not high, and they are prone to powder and slag, which is very disadvantageous in full heat exchangers.

[0006] The Chinese patent with publication number CN100348304C discloses a composite support liquid membrane and its preparation method. The composite support liquid membrane prepared by the invention has a three-layer structure, with a porous support layer in the middle and ultra-thin skin layers on both sides; the liquid membrane phase is fixed inside the porous support layer, and the liquid membrane phase is a LiCl solution with a mass fraction of 20% to 45%, which has strong hygroscopicity and low volatility; the ultra-thin skin layer is a polyvinylidene fluoride membrane, which is a hydrophobic membrane and protects the composite support liquid membrane. However, the disadvantage of the three-layer membrane structure is that the flow rate is small, and because the membrane layer is thick, the liquid stays in the membrane for a long time after expansion, and the thermal conductivity is poor, which cannot meet the latest international requirements for full heat exchangers. Summary of the invention

[0007] In order to solve the shortcomings of the full heat exchange membrane described in the above-mentioned prior art, the present invention provides a modified TPU nanofiber membrane and a preparation method thereof, wherein the modified TPU nanofiber membrane controls the enrichment of the modifier fluorinated biphenyl on the polyester TPU fiber by adjusting the humidity, thereby regulating the densified pore structure of the modified TPU nanofiber membrane obtained, thereby achieving improved mechanical properties, moisture permeability and hydrolysis resistance.

[0008] In a first aspect, the present invention provides a modified TPU nanofiber membrane, which comprises the following raw materials by mass percentage: 40-45% of 4,4'-diphenylmethane diisocyanate, 32-35% of 1,4-butanediol, 19.9-21% of adipic acid and 2-5% of a modifier.

[0009] In some embodiments of the present invention, the preparation process of the modifier comprises the following steps: putting a perfluorodicarboxylic acid into a reaction container filled with an organic solvent 1, filling it with an inert gas, then dropping a condensation agent and a promoter therein at -20 to -10°C, stirring for 1-2 hours, and then adding 2,2-bis(4-aminophenyl)hexafluoropropane, heating the reaction system to 50-70°C for amidation reaction, reacting for 3-5 hours, filtering, washing and drying the precipitated crystals to obtain the modifier.

[0010] In some embodiments of the present invention, the perfluorodicarboxylic acid is a carboxylic acid-terminated perfluoroalkyl diacid, and contains 3-8 carbon atoms.

[0011] In some embodiments of the present invention, the condensing agent is at least one of dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.

[0012] In some embodiments of the present invention, the accelerator is at least one of 4-dimethylaminopyridine, 4-pyrrolidinopyridine, N-hydroxysuccinimide, 1-decylbenzotriazole, and 2-hydroxy-5-amino-1,3,4-thiadiazole. In some embodiments of the present invention, the mass ratio of the fluorinated dicarboxylic acid to 2,2-bis(4-aminophenyl)hexafluoropropane is 60-76:67-80.

[0013] In some embodiments of the present invention, the organic solvent 1 is selected from at least one of dichloromethane, chloroform, and dimethylformamide.

[0014] In the present invention, the above-mentioned modifier is prepared by an amidation reaction between a perfluoroalkyl acid and 2,2-bis(4-aminophenyl)hexafluoropropane, a fluorine-containing substance containing an aniline group. The obtained modifier molecule contains a large number of fluorine atoms. Adding a small amount of it to TPU can improve the hydrophobicity of the TPU resin and protect the amide group in the TPU resin molecule from being easily hydrolyzed.

[0015] In a second aspect, the present invention provides a method for preparing the modified TPU nanofiber membrane, comprising the following steps:

[0016] S1: Add a measured amount of 1,4-butanediol to a reactor containing an organic solvent 2, heat to 100-120°C, dehydrate under vacuum for 1-2 hours, then cool to 60-75°C, add a measured amount of 4,4'-diphenylmethane diisocyanate and a catalyst, and then heat to 80-90°C, and keep the temperature for reaction for 2-3 hours;

[0017] S2: Cool the reaction system of S1 to 60-75°C, add measured adipic acid and modifier, stir rapidly, raise the system temperature to 80-90°C, pour into a mold coated with a release agent, and degas in an oven for 6-8 hours. Then, prepare the modified TPU nanofiber membrane on a receiving substrate at a spinning speed of 50-100r / min under RH30-80%.

[0018] In the preparation method provided by the present invention, the modified TPU nanofiber membrane pore structure is achieved by adjusting the amount of modifier added and the spinning humidity. During spinning, as the solvent evaporates and the steam diffuses into the fiber membrane, a viscosity gradient of the modified TPU resin is formed on the membrane section, and phase separation occurs in the fiber membrane. The rapid volatilization of the solvent will reduce the surface temperature of the solution, causing the steam to condense on the surface of the solution to form small water droplets. As the number increases and the volume increases, the water droplets on the surface eventually form a honeycomb-like close arrangement under the action of capillary forces. Moreover, the higher the air humidity, the more water enters, the slower the curing speed, and finally the smaller the cellular pores of the modified TPU nanofiber membrane, especially inside the membrane, the pore diameter is smaller than the pore diameter on the surface. In addition, due to the fluorine-containing hydrophobic structure of the modifier, as the solvent migrates outward, the modifier will also self-enrich the surface, forming a polymer cortex on the surface of the liquid film, inhibiting the rate of water migration inward. Ultimately, the surface of the modified TPU nanofiber membrane on the air side is looser than the internal structure, and the surface of the fiber membrane has a large number of pinholes.

[0019] If the amount of modifier is too large, the surface of the modified TPU nanofiber membrane will accumulate more fluorine-containing hydrophobic structures, the pore size formed on the surface will become larger, and water will easily enter the interior of the membrane through larger pores, affecting the formation of the internal dense pore structure; moreover, the humidity of the steam environment must also be strictly controlled. If the humidity is too low, the modifier cannot achieve the ideal content enrichment on the membrane surface, and the hydrophobicity of the membrane cannot be improved. If the humidity is too high, the modifier will migrate to the membrane surface in large quantities, and the connectivity between the internal pores will deteriorate, and a densified pore structure cannot be formed. In summary, when spinning to prepare the modified TPU nanofiber membrane, the control of the modifier and the ambient humidity must be within the range that meets the conditions.

[0020] In some embodiments of the present invention, the organic solvent 2 may be, but is not limited to, dimethylformamide (DMF), dimethylacetamide (DMA), dioxane, tetrahydrofuran, methyl isobutyl ketone, dimethyl sulfoxide, toluene, and the like.

[0021] In some embodiments of the present invention, the catalyst is at least one of a tertiary amine and an organotin. Specifically, the tertiary amine includes triethylenediamine, triethylamine, trimethylbenzylamine, dimethylethanolamine, etc., and the organotin includes stannous octoate, dibutyltin dilaurate, etc., and the added amount is 0.03-0.05wt% of the total reaction system.

[0022] In some embodiments of the present invention, the spinning conditions in S2 are: temperature of 15-30° C., voltage of 25-50 kV, and injection speed of the spinning mixture of 1-5 ml / h.

[0023] In some embodiments of the present invention, the receiving substrate is one of non-woven fabric, glossy paper, aluminum foil, and metal mesh.

[0024] Beneficial effects: Compared with the prior art, the present invention innovatively adds a fluorine-containing hydrophobic structure modifier to the TPU resin, and controls the pore structure of the modified TPU nanofiber membrane by controlling the humidity during the spinning stage:

[0025] 1. The volatilization of the solvent and the entry of steam make the modifier in the spinning solution gradually enriched on the membrane surface, and finally form a hydrophobic layer, which improves the hydrophobicity of the modified TPU nanofiber membrane. At the same time, the internal modifier promotes the close arrangement of the internal pores, forming a densified pore structure, which helps to enhance the mechanical properties of the modified TPU nanofiber membrane and reduce deformation;

[0026] 2. Due to the loss of solvent, the TPU resin forms a viscosity gradient in the membrane cross section, which ultimately makes the surface structure of the modified TPU nanofiber membrane on the air-side looser than the structure on the receiving matrix side, forming cellular pores, while the internal pore size is smaller than the pore size on the air-side, which is beneficial to the moisture permeability of the modified TPU nanofiber membrane. DETAILED DESCRIPTION

[0027] The present invention is described in further detail below in conjunction with examples. It should be noted that the following embodiments and comparative examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various improvements within the concept of the present invention may be carried out without departing from the gist or scope of the present invention.

[0028] The following is an exemplary description of the preparation process of the modifier used in the embodiment:

[0029] Modifier-1

[0030] 12 g of perfluoromalonic acid was put into a reaction container containing 150 ml of dichloromethane, and nitrogen was filled into the reaction container. Then, 0.7 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.14 g of N-hydroxysuccinimide were added dropwise thereto at -10°C. After stirring for 2 hours, 14 g of 2,2-bis(4-aminophenyl)hexafluoropropane was added, and the reaction system was heated to 50°C for amidation reaction. After reacting for 3 hours, the precipitated crystals were filtered out, the filtrate was mixed with ether, the crystals were filtered out again, anhydrous sodium sulfate was added to the filtrate for drying, and dichloromethane was removed in vacuo to obtain the modifier-1.

[0031] Modifier-2

[0032] 14 g of perfluoroglutaric acid was put into a reaction container containing 150 ml of dichloromethane, and nitrogen was filled into the reaction container. Then, 0.715 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.429 g of N-hydroxysuccinimide were added dropwise thereto at -5°C. After stirring for 2 hours, 16 g of 2,2-bis(4-aminophenyl)hexafluoropropane was added, and the reaction system was heated to 60°C for amidation reaction. After reacting for 4 hours, the precipitated crystals were filtered out, the filtrate was mixed with ether, the crystals were filtered out again, anhydrous sodium sulfate was added to the filtrate for drying, and dichloromethane was removed in vacuo to obtain the modifier-2.

[0033] Modifier-3

[0034] 22.8 g of perfluorooctanedioic acid was put into a reaction container containing 150 ml of dichloromethane, and nitrogen was filled into the reaction container. Then, 1.6 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.32 g of N-hydroxysuccinimide were added dropwise thereto at -5°C. After stirring for 2 hours, 24 g of 2,2-bis(4-aminophenyl)hexafluoropropane was added, and the reaction system was heated to 70°C for amidation reaction. After reacting for 5 hours, the precipitated crystals were filtered out, the filtrate was mixed with ether, the crystals were filtered out again, anhydrous sodium sulfate was added to the filtrate, dried, and dichloromethane was removed in vacuo to obtain the modifier-3.

[0035] Example 1

[0036] S1: Add 1,4-butanediol accounting for 32% of the total mass of the raw materials into a reactor filled with toluene, heat to 100°C, dehydrate under 0.67 kPa vacuum for 1 hour, then cool to 60°C, add 4,4'-diphenylmethane diisocyanate accounting for 45% of the total mass of the raw materials and 0.03% of triethylamine, then heat to 80°C and keep warm for reaction for 3 hours;

[0037] S2: The reaction system of S1 was cooled to 60°C, 20.97% of adipic acid and 2% of modifier-1 accounting for the total mass of the raw materials were added, and the system temperature was raised to 80°C, poured into a mold coated with a release agent, and aged and degassed in an oven at 50°C for 6 hours. Then, the modified TPU nanofiber membrane was prepared on a non-woven fabric at a spinning speed of 50r / min under RH30%, the spinning temperature was 15°C, the voltage was 25kV, and the infusion rate was 1ml / h.

[0038] Example 2

[0039] S1: Add 1,4-butanediol accounting for 35% of the total mass of the raw materials into a reactor filled with toluene, heat to 110°C, dehydrate under 0.67 kPa vacuum for 1 hour, then cool to 60°C, add 4,4'-diphenylmethane diisocyanate accounting for 42% of the total mass of the raw materials and 0.03% of dibutyltin dilaurate, then heat to 80°C and keep warm for reaction for 3 hours;

[0040] S2: The reaction system of S1 was cooled to 70°C, 19.97% of adipic acid and 3% of modifier-2 accounting for the total mass of the raw materials were added, and the system temperature was raised to 80°C, poured into a mold coated with a release agent, and aged and degassed in an oven at 50°C for 7 hours. Then, the modified TPU nanofiber membrane was prepared on glossy paper at a spinning speed of 80r / min under RH50%, the spinning temperature was 20°C, the voltage was 35kV, and the infusion rate was 3ml / h.

[0041] Example 3

[0042] S1: Add 1,4-butanediol accounting for 32% of the total mass of the raw materials into a reactor filled with toluene, heat to 120°C, dehydrate for 2 hours under 0.67 kPa vacuum, then cool to 70°C, add 4,4'-diphenylmethane diisocyanate accounting for 42% of the total mass of the raw materials and 0.05% of dibutyltin dilaurate, then heat to 90°C and keep warm for reaction for 2 hours;

[0043] S2: The reaction system of S1 was cooled to 70°C, 20.95% of adipic acid and 5% of modifier-3 accounting for the total mass of the raw materials were added, and the system temperature was raised to 80°C, poured into a mold coated with a release agent, and aged and degassed in an oven at 50°C for 8 hours. Then, the modified TPU nanofiber membrane was prepared on aluminum foil at a spinning speed of 100 r / min under RH80%, the spinning temperature was 30°C, the voltage was 50 kV, and the infusion rate was 5 ml / h.

[0044] Example 4

[0045] The preparation process is similar to that of Example 3, except that the spinning humidity is 20%.

[0046] Example 5

[0047] The preparation process is similar to that of Example 3, except that the spinning humidity is 90%.

[0048] Comparative Example 1

[0049] The preparation process is similar to that of Example 3, except that the addition amount of the modifier is 1%.

[0050] Comparative Example 2

[0051] The preparation process is similar to that of Example 3, except that the addition amount of the modifier is 6%.

[0052] Comparative Example 3

[0053] The preparation process is similar to that of Example 3, except that no modifier is added.

[0054] The modified TPU nanofiber membranes prepared in the above examples and comparative examples were tested as follows:

[0055] Surface contact angle: Cut the film into long strips, stick the front and back sides of the film on a glass slide with double-sided tape, and measure the contact angle on a KRUSS-DSA100 contact angle meter using distilled water by dripping method;

[0056] Tensile strength: in accordance with GB / T12824-2002 standard;

[0057] Tensile strength: in accordance with GB / T528-1998 standard, the test conditions are room temperature 25℃, tensile machine loading speed 50mm / min;

[0058] Water vapor permeability: in accordance with GB / T 12704.2-2009 "Test method for water vapor permeability of textile fabrics Part 2: Evaporation method".

[0059] The test results are shown in Table 1:

[0060]

[0061] From the data in Table 1, it can be seen that the modified TPU nanofiber membranes obtained in Examples 1-5 have excellent hydrophobicity, the contact angle between the surface and distilled water is not less than 116°, and the tensile strength is not less than 135N. The results show that the deformation resistance of the modified TPU nanofiber membrane is greatly improved (compared with the results of Comparative Example 3); the tensile strength is greater than 9000 g / (m 2 •24h) water permeability results show that the mechanical properties and water permeability of the modified TPU nanofiber resin are improved simultaneously.

[0062] The results of Examples 4-5 show that changes in spinning humidity will affect the hydrophobicity of the surface of the modified TPU nanofiber membrane and the moisture permeability of the membrane. This may be because excessive or insufficient humidity affects the formation of the pore structure inside the membrane.

[0063] The results of Comparative Example 2 show that the amount of the modifier added should not be too much. Although the presence of too much fluorinated biphenyl hydrophobic structure will also increase the hydrophobicity of the modified TPU nanofiber membrane, the moisture permeability of the membrane is greatly reduced. This may be because the hydrophobic structure on the membrane surface blocks the entry of steam.

[0064] In summary, the modified TPU nanofiber membrane provided by the present invention has excellent hydrophobicity, mechanical properties and moisture permeability, can effectively avoid the hydrolysis of TPU molecules, reduce deformation, and achieve efficient full heat exchange, and has considerable application prospects in the field of TPU fiber membranes.

Claims

1. A modified TPU nanofiber membrane, characterized in that: The raw materials are as follows, calculated by mass percentage: 40-45% of 4,4'-diphenylmethane diisocyanate, 32-35% of 1,4-butanediol, 19.9-21% of adipic acid and 2-5% of a modifier; The preparation process of the modifier comprises the following steps: putting a perfluorodicarboxylic acid into a reaction container containing an organic solvent 1, filling it with an inert gas, then dropping a condensation agent and a promoter therein at -20 to -10°C, stirring for 1-2 hours, then adding 2,2-bis(4-aminophenyl)hexafluoropropane, heating the reaction system to 50-70°C for amidation reaction, reacting for 3-5 hours, filtering the precipitated crystals, drying the filtrate, and removing the solvent in vacuo to obtain the modifier; The preparation method of the modified TPU nanofiber membrane comprises the following steps: S1: Add a measured amount of 1,4-butanediol to a reactor containing an organic solvent 2, heat to 100-120°C, dehydrate under vacuum for 1-2 hours, then cool to 60-75°C, add a measured amount of 4,4'-diphenylmethane diisocyanate and a catalyst, and then heat to 80-90°C, and keep the temperature for reaction for 2-3 hours; S2: Cool the reaction system of S1 to 60-75°C, add measured adipic acid and modifier, stir rapidly, raise the system temperature to 80-90°C, pour into a mold coated with a release agent, and degas in an oven for 6-8 hours. Then, prepare the modified TPU nanofiber membrane on a receiving substrate at a spinning speed of 50-100r / min under RH30-80%.

2. The modified TPU nanofiber membrane according to claim 1, characterized in that: The perfluorodicarboxylic acid is a carboxylic acid-terminated perfluoroalkyl diacid, and contains 3-8 carbon atoms.

3. The modified TPU nanofiber membrane according to claim 1, characterized in that: The condensing agent is at least one of dicyclohexylcarbodiimide, N,N-diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and the added amount is 0.5-1% of the mass of the reaction system.

4. The modified TPU nanofiber membrane according to claim 1, characterized in that: The accelerator is at least one of 4-dimethylaminopyridine, 4-pyrrolidinopyridine, N-hydroxysuccinimide, 1-decylbenzotriazole, and 2-hydroxy-5-amino-1,3,4-thiadiazole, and the added amount is 0.1-0.3% of the total mass of the reaction system.

5. The modified TPU nanofiber membrane according to claim 1, characterized in that: The catalyst is hydrochloric acid or 98% sulfuric acid.

6. The modified TPU nanofiber membrane according to claim 1, characterized in that: The mass ratio of the perfluorodicarboxylic acid to 2,2-bis(4-aminophenyl)hexafluoropropane is 60-76:67-80.

7. The modified TPU nanofiber membrane according to claim 1, characterized in that: The spinning conditions in S2 are: temperature of 15-30° C., voltage of 25-50 kV, and injection speed of the spinning mixture of 1-5 ml / h.

8. The modified TPU nanofiber membrane according to claim 1, characterized in that: The receiving substrate is one of non-woven fabric, glossy paper, aluminum foil and metal mesh.

Citation Information

Patent Citations

  • Composite support liquid film and its preparing method

    CN100348304C

  • Polyether imide-base dehumidification membrane

    JP1999090194A

  • Vapor membrane dehumidification for air cycle environment control system

    WO2003041844A1

  • Fluorine-containing water-resistant polyamide 6 and preparation method thereof

    CN113024803A

  • Green environment-friendly waterborne polyurethane waterproof breathable nanofiber membrane and preparation method thereof

    CN115595724A